Diversifikasi Produk Olahan Kopi Menjadi Sabun Kopi (Sapo Coffea) - Sakila Sakila; Wiri Wirastuti; Harnida Wahyuni Adda (Institut Nalanda, 2023)
Coffee has high economic value and is a very promising export commodity for Indonesia. Lembantongoa Village is one of the Robusta and Arabica coffee producing villages which has good potential in Sigi Regency. So far the coffee products sold by the people in the village are coffee beans. The utilization of coffee in Lembantongoa village is still limited to coffee beans. The coffee beans that have been collected are then further managed at the production house. Coffee beans under size 5 are coffee beans that are not included in the coffee criteria for consumption because they will affect the taste of the coffee drink. Coffee beans that are not sorted will become coffee waste that is not used and will damage the environment. Therefore, unsorted coffee product development is carried out to become coffee soap in order to increase its selling value. Making coffee soap is done traditionally to avoid chemicals. This writer's activity was able to produce processed coffee soap products that were packaged under the name Letofie. The results of testimonials from consumers who have tried are very useful for skin beauty.